Morton’s Neuroma in Physically Active Individuals: Etiology, Clinical Presentation, and Therapeutic Strategies - Nowaczek, Patrycja; Minik, Bartosz; Częczek, Kacper; Cieślewicz, Karolina; Szymańska-Zdyb, Kinga; Braksal, Barbara; Mirkowski, Krzysztof; Miroński, Adam; Szurek, Zuzanna Wanda; Chyła, Zofia Julia (Quality in Sport, 2026)
Background. Morton’s neuroma is one of the most common causes of forefoot pain, particularly among physically active individuals. This condition is a compressive neuropathy of the interdigital nerve and significantly affects sports participation and patients’ quality of life. Aim. The aim of this review article is to summarize current knowledge regarding the pathophysiology, diagnosis, and treatment methods of Morton’s neuroma, with particular emphasis on physically active populations and return-to-sport outcomes. Material and methods. A review of scientific literature available in the PubMed database was conducted, including clinical studies, systematic reviews, and meta-analyses published in recent years. Publications addressing etiology, clinical presentation, diagnosis, and both conservative and surgical treatment options were analyzed. Results. Morton’s neuroma is most commonly located in the third intermetatarsal space and presents with burning or stabbing pain accompanied by paresthesia, typically exacerbated during weight-bearing activities. Diagnosis is primarily based on clinical examination supported by imaging modalities such as ultrasonography and magnetic resonance imaging. Conservative treatment, including footwear modification, orthotic insoles, and corticosteroid injections, is considered first-line therapy and may provide significant pain relief. In refractory cases, interventional methods such as radiofrequency ablation or surgical treatment are employed, both of which demonstrate high effectiveness, although they carry a risk of complications. Conclusions. Morton’s neuroma represents a significant issue in sports medicine and requires a comprehensive diagnostic and therapeutic approach. Early diagnosis and appropriately selected treatment can effectively reduce symptoms and enable return to physical activity. Further studies are needed to optimize treatment strategies and evaluate long-term therapeutic outcomes.